Educational Management Based on Local Wisdom (Descriptive Analytical Studies of Culture of Local Wisdom in West Kalimantan) - Hamid Darmadi (JETL (Journal of Education, Teaching and Learning), 2018)
Education is a deliberate and planned deliberate effort to foster the development and potential of individual self-learners "learners" in order to benefit their life interests both as individuals and as members of the community. Education is one form of human culture because it must be seen as an activity that is always dynamic, following the acceleration of the rate of change and the dynamics of the culture of the community. Through education is expected to be organized the basis of values, thinking, and morality of the nation, in order to be able to produce a formidable generation in faith, personality, rich in intellectuality, and superior in the mastery of technology and information. For that, we need education based on local wisdom. The purpose of education based on local wisdom is in accordance with that has been stated in the Law. 20 Year 2003 About Sisdiknas Article 3, states that: "National education functions to develop the ability and form the character and civilization of a dignified nation in order to educate the nation's life". Local wisdom education is part of the culture of a society that can not be separated from the language of society itself. Local wisdom is passed down from generation to generation through word-of-mouth. Local wisdom is in folklore, proverbs, songs, and people's games. Local wisdom as a knowledge found by a particular local community through a collection of experiences in trying and integrated with an understanding of the culture and nature of a place. Along with the development of the age along with the rapid flow of information and technology are constantly changing, there is a tendency of local wisdom began marginalized. It needs to be socialized to the younger generation so that the culture of wisdom is not lost in time.